1997
DOI: 10.1021/ie970386v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Catalytic Activity of WNiMo/Al2O3 Catalyst for Hydrodenitrogenation of Pyridine

Abstract: Various transition-metal catalysts supported on γ-alumina were prepared and applied for the hydrodenitrogenation (HDN) of pyridine. The NiMo/Al 2 O 3 catalyst showed higher activity than the Mo/Al 2 O 3 catalyst. On the basis of the results of reaction experiments and measurements of IR and TPR, the enhancement in the HDN activity with nickel addition could be attributed more to the improvement in the reducibility of molybdenum than to the effect of Bro ¨nsted acid site. Tungsten impregnated on the NiMo/Al 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…As can be seen from Fig. 2a [5,23], this suggests that more than one type of Lewis acid sites exist on the surface of cAl 2 O 3 . When potassium and molybdenum were incorporated into the alumina support, the intensity of all the bands for Lewis acid sites was distinctly weakened, which most probably because that K 2 CO 3 is alkaline and it can reduce acidity by neutralizing some Lewis acid sites on the surface of the catalysts.…”
Section: Surface Acid-base Propertiesmentioning
confidence: 77%
“…As can be seen from Fig. 2a [5,23], this suggests that more than one type of Lewis acid sites exist on the surface of cAl 2 O 3 . When potassium and molybdenum were incorporated into the alumina support, the intensity of all the bands for Lewis acid sites was distinctly weakened, which most probably because that K 2 CO 3 is alkaline and it can reduce acidity by neutralizing some Lewis acid sites on the surface of the catalysts.…”
Section: Surface Acid-base Propertiesmentioning
confidence: 77%
“…According to the XPS results, the ratios of Ce 3+ /Ce 4+ were different in various samples. It has been reported that Mo 6+ species can be present in both tetrahedral and octahedral coordination (Park et al, 1997). Therefore, it can be inferred that the difference in H 2 consumption for various samples was likely to correlate with the formation of subtly different surface structure of Ce and Mo oxide species, resulting from different catalyst preparation methods.…”
Section: H 2 -Tpr Resultsmentioning
confidence: 99%
“…And a catalyst which is active for soot oxidation is usually attached to lower the soot ignition temperature [11][12][13]. Owing to the high price of the current choice of Pt catalyst, many attempts have been made to develop Pt-free catalysts which include perovskite-type oxides, spinel type oxides, alkaline or heavy metal oxides, mixtures of halides with vanadates or molybdates and so on [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%